"Nobody cares about you as a group of people": a mixed methods study of women living in congregate social housing in Ontario, Canada. Issue 1 (2nd January 2021) - Marshall, Carrie Anne; Tjörnstrand, Carina; Downs, Emily; Devries, Rebecca; Drake, Fiona
ABSTRACT: Guided by the social model of disability, we carried out this exploratory study to understand the health and psychosocial needs of women living in social housing in Ontario, Canada. Using a sequential, mixed-methods design, we interviewed 19 women using a 126-item quantitative interview including six standardized measures exploring indicators of psychosocial well-being. From these findings, we designed a qualitative interview protocol and returned to participants. We calculated descriptive statistics for quantitative variables and analyzed qualitative data using thematic analysis. Participants reported a median of six unmet basic psychosocial needs (range 1–16; IQR = 6), a high prevalence of health conditions and associated disability with scores falling above the 80 th percentile on all subtests of a disability measure. Qualitative findings revealed that participants were living in an environment that made it challenging to meet their basic needs and felt abandoned by community supports. A persistent lack of safety led to self-isolation, which negatively influenced mental well-being. Social housing is aimed at alleviating poverty and its associated harms, yet women face multiple barriers to meeting their basic needs through existing supports and continue to experience poverty. Social housing can be disabling environments for women living in poverty.